PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN TEKNIK 3N (NITENI, NIROKE, NAMBAHI) - Fatoni, L. Hendra (Universitas Hamzanwadi, 2024)
This research aims to describe the improvement of poetry writing skills using the 3N technique and detail changes in student behavior after participating in lessons employing this technique, which holds significant implications for the development of theories in Indonesian language and literature education. Employing a two-cycle classroom action research design with students from class XA at SMAN 1 Sakra Timur, the analysis results indicate a 20.08% increase in the average class score in poetry writing skills using the 3N technique from cycle I to cycle II, along with a 43.3% change in student behavior. The average observation score increased from 60 in cycle I to 86 in cycle II, this shows a change in student behavior in a more positive direction. This shows that improving poetry writing skills is greatly influenced by student behavior. Students who initially tended to behave negatively and underestimate explanations, changed to become happier, active and serious in learning. They increasingly show enthusiasm and enjoy the learning process, so that the class atmosphere becomes more lively and orderly, and they are able to complete assignments well.